PEMETAAN WILAYAH LAHAN KERING MENGGUNAKAN DATA PENGINDERAAN JAUH - Arthur Gani Koto (Akademika, 2017)
Dry land occupies the largest area (90%) and has a strategic position in agricultural development activities in Indonesia. The biggest potential of natural resources in the agricultural sector in the district was reached 40.26%. One of the data provider of effective and efficient in terms of development activities and development of the region is remote sensing data. The purpose of this study is to map the area of dry land with the help of remote sensing data. Landsat imagery 8 extracted to obtain land cover information which is then further processed to produce a land use classification is based on the knowledge based classification. Analyzed land use to obtain the map of dry land. The results showed that the District of Wonosari has an area of dry land scattered in all districts and has an area of 185. 733 km2. Dry land area consists of mixed farms (162.811,8 km2) and bare land (22.921,2 km2). Tanah kering menempati area terbesar (90%) dan memiliki posisi strategis dalam kegiatan pembangunan pertanian di Indonesia. Potensi sumber daya alam terbesar di sektor pertanian di kabupaten ini mencapai 40,26%. Salah satu penyedia data yang efektif dan efisien dalam hal kegiatan pengembangan dan pengembangan kawasan adalah data penginderaan jauh. Tujuan dari penelitian ini adalah untuk memetakan daerah lahan kering dengan bantuan data penginderaan jarak jauh. Citra landsat 8 diekstraksi untuk mendapatkan informasi tutupan lahan yang kemudian diproses lebih lanjut untuk menghasilkan klasifikasi penggunaan lahan berdasarkan klasifikasi berbasis pengetahuan. Menganalisis penggunaan lahan untuk mendapatkan peta lahan kering. Hasil penelitian menunjukkan bahwa Kabupaten Wonosari memiliki lahan kering yang tersebar di semua kecamatan dan memiliki luas wilayah 185. 733 km2. Luas lahan kering terdiri dari lahan pertanian campuran (162,811,8 km2) dan lahan kosong (22.921,2 km2).